Interactions of ferro-nanoparticles (hematite and magnetite) with reservoir sandstone: implications for surface adsorption and interfacial tension reduction - Ali, A.M. (China University of Petroleum Beijing, 2020)
There are a few studies on the use of ferro-nanofluids for enhanced oil recovery, despite their magnetic properties; hence, it is needed to study the adsorption of iron oxide (Fe2O3 and Fe3O4) nanoparticles (NPs) on rock surfaces. This is important as the colloidal transport of NPs through the reservoir is subject to particle adsorption on the rock surface. Molecular dynamics simulation was used to determine the interfacial energy (strength) and adsorption of Fe2O3 and Fe3O4 nanofluids infused in reservoir sandstones. Fourier transform infrared spectroscopy and X-ray photon spectroscopy (XPS) were used to monitor interaction of silicate species with Fe2O3 and Fe3O4. The spectral changes show the variation of dominating silicate anions in the solution. Also, the XPS peaks for Si, C and Fe at 190, 285 and 700Â eV, respectively, are less distinct in the spectra of sandstone aged in the Fe3O4 nanofluid, suggesting the intense adsorption of the Fe3O4 with the crude oil. The measured IFT for brine/oil, Fe2O3/oil and Fe3O4/oil are 40, 36.17 and 31Â mN/m, respectively. Fe3O4 infused with reservoir sandstone exhibits a higher silicate sorption capacity than Fe2O3, due to their larger number of active surface sites and saturation magnetization, which accounts for the effectiveness of Fe3O4 in reducing IFT. Â© 2020, The Author(s).